Risk and severity of herpes zoster in patients with rheumatoid arthritis receiving different immunosuppressive medications: a case–control study in Asia - Liao, Tsai-Ling (BMJ Open, 2017)
OBJECTIVE: Increasing evidence indicates that the risk of herpes zoster (HZ) is elevated in rheumatoid arthritis (RA). Little is known about the epidemiology of HZ in patients with RA in Asia. The aim of this study was to determine the risk factors and outcomes of HZ among patients with RA. DESIGN: A case–control study. SETTING: A medical centre in Asia. PARTICIPANTS: A total of 9025 newly diagnosed and eligible patients with RA (International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes 714.0) during the period 2001–2014. Among them, 275 (3.05%) were newly diagnosed with HZ (ICD-9-CM code 053.0) after the RA identification. As the control group, patients with RA without HZ were matched for age, gender and RA disease duration at the time of HZ infection with the RA-HZ case group at a ratio of 4:1, and a total of 1100 control subjects were selected. OUTCOME MEASURES: We estimated ORs using conditional logistic regression to investigate the risk and severity of HZ among patients with RA receiving different immunosuppressive medications. RESULTS: Exposure to corticosteroids (≥10 mg/day adjusted OR (aOR)=2.30, 95% CI 1.25 to 4.22, p=0.01), anti-tumour necrosis factor biologicals (aOR=2.07, 95% CI 1.34 to 3.19, p=0.001) and conventional synthetic disease-modifying anti-rheumatic drugs (methotrexate (aOR=1.98, 95% CI 1.43 to 2.76, p<0.001) and hydroxychloroquine (aOR=1.95, 95% CI 1.39 to 2.73, p<0.001)) was associated with an increased HZ risk in patients with RA. The association between the use of corticosteroids and HZ risk was dose-dependent (p(trend)<0.001). Time-to-HZ diagnosis among patients with RA receiving biological medications was significantly shorter than that in patients not receiving biological medications. A higher proportion of severe HZ and ophthalmic involvement was found in patients with RA receiving biologicals. CONCLUSIONS: There was an increased risk of HZ in patients with RA taking specific immunosuppressive medication. Biologicals used were associated with severe HZ occurrence. Therefore, it is important to closely monitor and prevent severe HZ complications during specific immunosuppressive therapy.